ACCURACY OF THE USE OF ANTITUBERCULOSIS DRUGS IN PATIENTS WITH PULMONARY TUBERCULOSIS COMORBID WITH TYPE 2 DIABETES MELITUS IN HOSPITAL X BEKASI CITY FOR THE PERIOD 2019-2022: ACCURACY OF THE USE OF ANTITUBERCULOSIS DRUGS IN PATIENTS WITH PULMONARY TUBERCULOSIS COMORBID WITH TYPE 2 DIABETES MELITUS IN HOSPITAL X BEKASI CITY FOR THE PERIOD 2019-2022 - rachmita arianti, Anisa; Dzakiya, Meisya Putri; Harahap, Nofria Rizki Amalia; Nathalia, Dede Dwi (Jurnal Mitra Kesehatan, 2024)
Introduction: Pulmonary tuberculosis is a chronic infection caused by the bacterium Mycobacterium tuberculosis. The disease can lead to severe complications, including diabetes, which increases the risk of death. In addition, the prevalence of TB-DM in Indonesia reaches 14.8%. Objective: This study was to evaluate the use of antituberculosis drugs in patients with pulmonary TB comorbid with diabetes mellitus using the right indication, right dose, and right drug indicators. Methods: The research design used was observational with a retrospective approach. This study used independent variables including age, gender, treatment profile, stage of treatment, correct drug, correct dose and correct indication. The sampling technique used was consecutive sampling. The sample of this study consisted of 62 outpatients who were analyzeddescriptively quantitatively using Microsoft Excel. Results: This study shows that the number of male (65%) and female (35%) patients with the majority age 46-55 years (45%). Lung TB drug use therapy is dominant OAT Kombipak (69.4%) and KDT (30.6%). Evaluation of drug use showed the level of indication accuracy of 100%, the right dose of 83.9%, and the right drug of 93.5%. Conclusion: Based on compliance with the "National Guidelines for TB Control" issued by the Ministry of Health of the Republic of Indonesia in 2016, the treatment provided to outpatient TB patients with DM comorbidity at Hospital X in Bekasi Cityfrom 2019 to 2022 showed a 100% accuracy rate for indications (62 patients), 83.9% accuracy rate for dosages (52 patients), and 93.5% accuracy rate for drug selection (58 patients).